Safety behaviors and speech treatment for adults who stutter. - Helgadottir, F; Menzies, R; Onslow, M; Packman, A; O'Brian, S (American Speech-Language-Hearing Association, 2014)
PURPOSE: Those with anxiety use safety behaviors when attempting to prevent negative outcomes. There is evidence that these behaviors contribute to the persistence of anxiety disorders. Safety behaviors have been prominent in the cognitive behavior therapy literature during the last decade, particularly with social phobia management. However, nothing is known of safety behavior use by those who stutter. This is surprising given the high prevalence of social phobia in the stuttering population who seek clinical help. METHOD: Clinical psychologists and speech-language pathologists (SLPs) created a list of safety behaviors that might be used by adults during treatment for stuttering. Participants were 160 SLPs who were asked whether they advised adults who stutter to use any of these safety behaviors. RESULTS: SLPs commonly recommend safety behaviors during stuttering management. Factor structures were found for the following 5 safety behavior categories: (a) general safety behaviors, (b) practice and rehearsal, (c) general avoidance, (d) choosing safe and easy people, and (e) control-related safety behaviors. CONCLUSIONS: There is a need to determine the frequency with which adults who receive stuttering treatment follow these clinician recommendations. In addition, there is a need to experimentally determine whether following such recommendations prevents fear extinction at long-term follow-up.